The development of Chinese character reading and knowledge in young children. (September 2021) - Zhang, Li; Zhou, Jing; Cao, Simin
Early reading and literacy are critical for helping children to become good readers, and character reading and knowledge are important aspects. However, few studies have investigated this issue. By drawing on 127 children between 4 and 6 years of age from five Level 1 kindergartens in Shanghai, this study examined the development of Chinese character reading and knowledge in young children. Character reading was assessed using the revised Chinese Communicative Development Inventory. Children's knowledge of Chinese characters was administered through three tasks, namely stroke-pattern recognition, visual memorization and component detection, and component positioning. Results indicated that children acquired some characters before formally learning to read and write. Both character reading and knowledge developed rapidly with age. Further, children's knowledge of Chinese characters was closely associated with their character reading. Findings suggest that children's interest and knowledge of characters should be fostered during the early years to prepare them to be successful readers.